(untitled) (Web of Teachers: Inderscience Research, 2025)
In the current article, it is observed that in the teaching of Applied Decorative Arts in modern times, there are changes in the requirements for the teacher’s personality and the functions that must be carried out during their professional activity. In contemporary education, it is emphasized that teachers who are capable of carrying out artistic-creative activities, possess the virtues of a creative personality, have acquired the knowledge, skills, and competencies necessary to implement this activity, and have developed reflective processes and innovative thinking are required.